Initial steps of insulin signaling and glucose transport are defective in the type 2 diabetic rat heart. - Desrois, M; Sidell, R; Gauguier, D; King, L; Radda, G; Clarke, K (2004)
OBJECTIVE: Whole body insulin resistance and diabetes are risk factors for cardiovascular diseases, yet little is known about insulin resistance in the diabetic heart. The aim of this work was to define the insulin response in hearts of the Goto-Kakizaki (GK) rat, a polygenic model of spontaneous type 2 diabetes. METHODS: We measured D[2-3H]glucose uptake before and after insulin stimulation, plus initial steps of the insulin signaling pathway after insulin infusion via the caudal vena cava in hearts from the male Wistar and spontaneously diabetic GK rats. RESULTS: Despite normal basal D[2-3H]glucose uptake, insulin-stimulated glucose uptake was 50% (p<0.03) lower in GK rat hearts compared with their Wistar controls. Total GLUT4 protein was depleted by 28% (p<0.01) in GK rat hearts. We found 31% (p<0.0001) and 38% (p<0.001) decreased protein levels of insulin receptor beta (IRbeta)-subunit and insulin receptor substrate-1 (IRS-1), respectively, in GK rat hearts with 37% (p<0.02) and 45% (p<0.01) lower insulin-stimulated tyrosine phosphorylation of these proteins. Owing to the decreased IRS-1 protein levels, GK rat hearts had a 41% (p<0.0001) decrease in insulin-stimulated IRS-1 protein association with the p85 subunit of phosphatidylinositol 3-kinase, despite normal phosphatidylinositol 3-kinase protein expression. Insulin-stimulated serine phosphorylation of protein kinase B was the same in all hearts, as was protein kinase B expression. CONCLUSION: We conclude that decreased insulin receptor beta, IRS-1 and GLUT4 proteins are associated with insulin resistance in type 2 diabetic rat hearts.